Rationalization of Action in Education Investment Decisions: Parents' Perceptions - Andy Prasetyo Wati; Sri Handayani; Durinda Puspasari; Jefry Aulia Martha (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
This research aims to see how the rationality of parents towards their decision to act in improving the quality of human resources owned by children through education. This is due to the problems that arise from various theoretical studies on